Creating good jobs an industry-based strategy - Ostermann, Petrus 1595-1657; Dyer, Barbara 1951- (The MIT Press, 2020)
"What makes a job good? A predictable schedule, regular paycheck, time off, health insurance, opportunities for training and advancement? What would it take to make more jobs better jobs, and what might be the limits to such improvement? The vertically integrated corporations of the past, with their career ladders, clear pay scales, and workers' benefits (from health insurance to PTO to pensions), have been gradually replaced by outsourcing and subcontracting, the use of staffing agencies, and increasing proportions of part-time and freelance workers. Globalization, technological change, market pressures favoring short-term gains, shifts in consumer demands, and declines in union membership have changed how workers and businesses operate in the economy. The demands of economic competition in the US have sent industries and employers to cutting labor costs any way they can.
Bevorzugte Informationsquelle: Landingpage (The MIT Press Direct), da weder Titelblatt noch Impressum vorhanden
Keywords: Employability / United States; Labor market / United States / History / 21st century; Employment forecasting / United States